Efektivitas Layanan Konseling Kelompok Melalui Teknik Poetry Therapy Untuk Mereduksi Academic Anxiety Pada Mahasiswa BK - Anna Ayu Herawati; Hadiwinarto Hadiwinarto; I Wayan Dharmayana (Teraputik: Jurnal Bimbingan dan Konseling)
Anxiety is a mental condition filled with worry and fear of what might happen, both related to limited problems and strange things. Anxiety caused by students will bring up problems related to motivation, achievement, and psychological impact. Anxiety experienced by students related to the academic burden, including in the preparation of the thesis is also called academic anxiety or academic anxiety. The purpose of this research is to: (1) describe the level of academix anxiety before being given group counseling services through poetry therapy techniques (2) describe the level of academix anxiety after being given group counseling services through poetry therapy techniques (3) the difference in levels of academix anxiety before and after given group counseling services through poetry therapy techniques. The research method used in this study is a pre-experimental design research. The sample in this study was 5th semester BK students who were indicated to have academic anxiety. This research uses One-Group Pretest-Posttest Design. The results of the study indicate that there is an effect of group counseling with poetry therapy techniques to reduce academic anxiety in students so that there can be a decrease in the level of anxiety experienced by students. This can be seen in the changes that occur from the results of the pretest and posttest with the average obtained before the action is 135 and after the action is given the average result is 97, supported by the results of the paired sample t-test hypothesis test which shows a significant value of 0.000 < 0.005. So from these results it was found that group counseling services with poetry therapy techniques were able to reduce academic anxiety experienced by BK students.